2020
DOI: 10.1186/s12879-020-05418-4
|View full text |Cite
|
Sign up to set email alerts
|

The wrong Spirochaete? Acute kidney injury in a returning traveller with syphilis – a case report

Abstract: Background Syphilis has seen an increased incidence in recent years and can have serious and irreversible consequences if left un-diagnosed and untreated. This case report describes a presentation of syphilis and acute kidney injury – a scenario sparsely described in existing literature. Case presentation This 43-year old Man who has Sex with Men (MSM) presented to the emergency department with a 3-week history of vomiting and headaches, progressing to include pyrexia. These symptoms started following his re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Compared with the control group, the syphilis group demonstrated higher alanine aminotransferase and glutamyl transpeptidase concentrations (28 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] vs. 18 [12][13][14][15][16][17][18][19][20][21][22][23] and 27 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] vs. 20 [13][14][15][16][17][18]...…”
Section: Organ Function May Exhibit Impaired Functionality In Patient...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the control group, the syphilis group demonstrated higher alanine aminotransferase and glutamyl transpeptidase concentrations (28 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] vs. 18 [12][13][14][15][16][17][18][19][20][21][22][23] and 27 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] vs. 20 [13][14][15][16][17][18]...…”
Section: Organ Function May Exhibit Impaired Functionality In Patient...mentioning
confidence: 99%
“…In a study, among 175 early cases of syphilis, 17 demonstrated liver injury, and 14 exhibited histopathological abnormalities in the liver; moreover, T. pallidum was detected in the livers of 7 cases, indicating its potential to induce hepatitis [10]. T. pallidum may also lead to syphilitic arthritis [11], renal impairment [12], vasculitis, bile duct injury [13], and pathological changes, including syphilitic proctitis, gastritis, and hepatitis [14]. Numerous case reports and epidemiological studies have reported that HIV infection-induced immunosuppression signi cantly hampers the ability to clear T. pallidum [15].…”
Section: Introductionmentioning
confidence: 99%